Requirements for the Application of Electronic Administration and its Obstacles from the point of view of Government School Principals in Zarqa Governorate and Proposals for its Activation - Alzaidaneen, Sajeda Salameh (Journal of Educational and Psychological Sciences, 2022)
The current study aimed at identifying the degree of requirements for the application of electronic administration and its obstacles, as well as suggestions and mechanisms for its application from the point of view of the principals of public schools in Zarqa Governorate, and to achieve the objectives of the study, the descriptive analytical approach was used. Where the study sample consisted of (153) male and female managers, a questionnaire was applied to them, which consisted of (31) items, distributed on three axes. As for the third axis, it represents the proposals and mechanisms for applying electronic management, and it includes (12) paragraphs, and its validity and stability indications have been verified. The study concluded that the degree of requirements for the application of electronic management was high, with an arithmetic mean (3.68 out 5) and that the degree of obstacles to applying electronic management was medium, with an arithmetic mean (3.56). Where their averages ranged between (3.77- 3.97), and they are: raising the financial capabilities necessary for the orbital application of electronic management, providing the ministry with financial and moral support for schools that apply management computerization, increasing financial allocations for training programs for school leaders in the field of electronic management, and providing financial support for research and studies In the field of information technology, The results did not show the presence of differences due to the variables of sex and educational qualification, and the presence of differences due to experience and in favor of those with experience (from 5 to less than 10 years).
Keywords: Electronic Administration; Electronic Administration Requirements; Electronic Administration Obstacles; Government School Principals